1996
DOI: 10.1093/rheumatology/35.9.898
|View full text |Cite
|
Sign up to set email alerts
|

Severe Osteoporosis Due to Systemic Mast Cell Disease: Successful Treatment With Interferon Alpha-2b

Abstract: SUMMARYWe describe a 33-yr-old man suffering from severe vertebral osteoporosis and urticaria pigmentosa due to systemic mast cell disease (SMCD). Because i.v. clodronate therapy could not prevent further vertebral fractures, an additional treatment with interferon alpha-2b was initiated. During 24 months of treatment, our patient had no further pain episodes, no new vertebral fractures were discovered, trabecular bone mineral density (BMD) increased significantly and urticarial symptoms improved. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 20 publications
1
48
0
7
Order By: Relevance
“…Malabsorption is generally managed with corticosteroids. Calcium supplementation and bisphosphonates are useful in the case of osteoporosis, and IFN is occasionally indicated [8,12,14,20]. Our series includes 3 patients with indolent SM who remained stable with symptomatic therapy only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malabsorption is generally managed with corticosteroids. Calcium supplementation and bisphosphonates are useful in the case of osteoporosis, and IFN is occasionally indicated [8,12,14,20]. Our series includes 3 patients with indolent SM who remained stable with symptomatic therapy only.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, symptomatic measures are employed first but generally are not successful. Ex vivo studies revealed that IFN could exert inhibitory effects on factor-dependent growth of mast cells from circulating progenitor cells in patients with SM and a number of clinical reports have shown IFN to be useful in the treatment of ASM [3,[7][8][9][10][11][12][21][22][23][24][25]. In the largest series of patients reported, Casassus et al treated 20 consecutive adult SM patients with IFN 1-5 MU/m 2 /day SQ, with progressive dose intensification over the first month of treatment, to a maximum of 6 months [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-a is often considered the first-line cytoreductive therapy in symptomatic SM; since the initial report in 1992 [79], several case reports or small series have shown IFN-a (IFN-a2b in most instances) to improve symptoms of MC degranulation, decrease BM MC infiltration, and ameliorate mastocytosis-related ascites/hepatosplenomegaly, cytopenias, skin findings, and osteoporosis [80][81][82][83][84][85][86][87][88][89][90][91][92]. IFN-a treatment is not uniformly effective [93], and the frequency of major response (i.e., complete resolution of one or more baseline 'C' findings) is 20-30%; the optimal dose and duration of IFN-a therapy for SM remain unclear, however concurrent administration of corticosteroids (prednisone) may improve its efficacy (up to 40% major response rate) and tolerability [87,94].…”
Section: Interferon (Ifn)-amentioning
confidence: 99%
“…[81][82][83][84] I obtain spine radiographs and measure BMD at the spine and hip by dual-energy x-ray absorptiometry (DXA) scans in all ISM patients. I ensure that all patients have an adequate intake of calcium and vitamin D. I optimize antimediator therapy in every case and institute bisphosphonate therapy when osteoporosis is documented.…”
Section: Malabsorption With Weight Loss Due To Gastrointestinal Mast mentioning
confidence: 99%